Identification, Recovery, and Refinement of Hitherto Undescribed Population-Level Genomes from the Human Gastrointestinal Tract - Laczny, Cedric C.; Muller, Emilie E. L.; Heintz-Buschart, Anna; Herold, Malte; Lebrun, Laura A.; Hogan, Angela; May, Patrick; de Beaufort, Carine; Wilmes, Paul (Frontiers in Microbiology, 2016)
Linking taxonomic identity and functional potential at the population-level is important for the study of mixed microbial communities and is greatly facilitated by the availability of microbial reference genomes. While the culture-independent recovery of population-level genomes from environmental samples using the binning of metagenomic data has expanded available reference genome catalogues, several microbial lineages remain underrepresented. Here we present two reference-independent approaches for the identification, recovery, and refinement of hitherto undescribed population-level genomes. The first approach is aimed at genome recovery of varied taxa and involves multi-sample automated binning using Canopy Clustering complemented by visualisation and human-augmented binning using VizBin post hoc. The second approach is particularly well-suited for the study of specific taxa and employs VizBin de novo. Using these approaches, we reconstructed a total of six population-level genomes of distinct and divergent representatives of the Alphaproteobacteria class, the Mollicutes class, the Clostridiales order, and the Melainabacteria class from human gastrointestinal tract-derived metagenomic data. Our results demonstrate that, while automated binning approaches provide great potential for large-scale studies of mixed microbial communities, these approaches should be complemented with informative visualisations because expert-driven inspection and refinements are critical for the recovery of high-quality population-level genomes.